THE DECLINING ASWAJA THEOLOGY KNOWLEDGE PRODUCTION: A Case Study of al-Jam’iyatul Washliyah in Medan City - Maulana Andi Surya (AL-TAHRIR, 2023)
Al-Jam’iyatul Washliyah (AW) and Aswaja theology are covered in this article. As a religious institution, AW acknowledges Aswaja’s ideology as the foundation for its mission. To maintain and develop Aswaja theology, AW utilizes educational institutions and recitation of the kitab kuning (yellow book) as a knowledge production for Aswaja theology. A question concerning the state of educational institutions today and the recitation of the Yellow Book at AW in Medan City was posed in order to comprehend the information presented. A case study about AW in Medan City is the qualitative research methodology that is employed. In addition, leaders, religious authorities, educators, and AW-related documents make up the primary  data source. According to his research, educational institutions that regularly support Aswaja books undergo internal changes and come to terms with the reality that teachers, or ustadh, are becoming less and less proficient in the classics. Additionally, a number of the study’s leaders—who were specialists in classic literature—passed away, which caused a setback to the kitab kuning study. Thus there was a downturn in the study of the kitab kuning. The results verify the weakening of the apparatus in AW that produces Aswaja theology.